GAMBARAN KEJADIAN PENYAKIT KULIT PADA MASYARAKAT PENGGUNA AIR SUNGAI KUANTAN - Resti Rulfima Sari; Safri Safri; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
People lived in the surrounding area of the river usually use river water for their daily needs. This habit certainly affects health status, especially integument diseases. This research was to find out how the description of the incidence of integument diseases in the community using the Kuantan River water. The research sample was 100 respondents who were taken based on the inclusion criteria using cluster sampling technique. The measuring instrument used a questionnaire and observation sheet to determine the type of integument disease. The analysis used univariate analysis to determine frequency distribution. The results showed 76 respondents were female (76.0%), 25 respondents were at the age of 26-35 years (25.0%), 52 respondents had elementary school education (52.0%), 25 respondents working as house wife (25%), 76 respondents earning <Rp. 2,500,000 (76.0%), and 54 respondents showed that integument related diseases were dermatitis (54.0%), 3 respondents had ulcers (3.0%). It is hoped that this research can be a source of information on the causes of skin diseases, especially dermatitis, and what factors influence integument diseases, so that people can reduce the use of polluted water and can apply Family Health Assignments.Keywords: Integument disease,s kuantan river water, society